2020
DOI: 10.1371/journal.pone.0231318
|View full text |Cite
|
Sign up to set email alerts
|

How does social capital affect individual health among the elderly in rural China?—Mediating effect analysis of physical exercise and positive attitude

Abstract: Background The elderly in rural areas comprise over half of the older population in China, and their health problems are a matter of great concern for the Chinese government and society. Among the many factors affecting health, social capital has generated much interest in academic research. Exploring the relationship between social capital and individual health among the elderly in rural China provides ways to improve the health of Chinese people, which has a positive impact on policy. Methods We selected 371… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…A follow-up study in the United Kingdom also showed that inconsistent social contact increases the risk of isolation and depression among the older population [ 24 ]. Consistently, several other studies also showed that high social capital among older adults in rural areas results in better mental health status [ 25 , 26 ].…”
Section: Introductionsupporting
confidence: 79%
“…A follow-up study in the United Kingdom also showed that inconsistent social contact increases the risk of isolation and depression among the older population [ 24 ]. Consistently, several other studies also showed that high social capital among older adults in rural areas results in better mental health status [ 25 , 26 ].…”
Section: Introductionsupporting
confidence: 79%
“…Previous studies show that bonding social capital comprising a connection between community members is often stronger among rural older adults, resulting in higher level of interpersonal trust, reciprocity and community cohesion [29,30]. With the rapid urbanization and changes in family structure, older adults in rural areas need to face more obstacles to get care and support from family members (i.e., sons and daughters) who have increasingly migrated to urban areas for education and work opportunities [31,32]. Some of them relocate to the town or city with their family members, which would affect the social capital of rural older adults, thereby affecting their health.…”
Section: Introductionmentioning
confidence: 99%
“…With declining age, adherence to a healthy lifestyle becomes a complex endeavour hindered by multiple factors [ 19 , 20 ]. Other than access and knowledge, social support and the notion of Social Capital is increasingly recognised as an important element in determining the likelihood of adopting a healthy lifestyle in older age [ 19 , 21 , 22 , 23 , 24 , 25 ]. Social Capital as a notion describes the sense of belonging and being part of a supportive society that shares the same values and creates benefits for the individual and the society as a whole [ 26 ].…”
Section: Introductionmentioning
confidence: 99%